The Influence of Card Sort Active Learning Model on Learning Outcomes of PPKn Class V SDN 91 Palembang - Fadilah, Fadilah; Disurya, Ramanata; Dedy, Adrianus (Yayasan Sembilan Pemuda Indonesia, 2023)
This study examines the effect of the Active Learning model type Card Sort which aims to determine whether there is an influence on the learning outcomes of Civics class V SDN 91 Palembang. The approach used is quantitative experiment. Research design with quasi-experimental design Pretest-Posttest control group design. From data processing, it was obtained that the average pretest value for the experimental class was 49.40, the control class was 43.00 and the posttest average value for the experimental class was 90.60, the control class was 51.80. Based on the normality test it was stated that the sample came from a normal population. Based on the homogeneity test it was stated that the sample came from a homogeneous population, then based on the hypothesis test it was known that t-count was 14.916, to compared with t-table at a significant level of 0.025 with dk n - 1 = 25-1 = 24, obtained a significant level of 0.025 = 0.594. Thus Ho (null hypothesis) is rejected and Ha (alternative hypothesis) is accepted. Based on the results of the analysis and discussion of test data, it can be concluded that learning outcomes have an effect after being given treatment using the Card Sort Active Learning model in class V SD Negeri 91 Palembang.